Compound heterozygosity for two GHR missense mutations in a patient affected by Laron Syndrome: a case report - Stefania Moia; Daniele Tessaris; Silvia Einaudi; Luisa de Sanctis; Gianni Bona; Simonetta Bellone; Flavia Prodam (BMC, 2017)
Abstract Background Mutations localized in the Growth Hormone Receptor (GHR) gene are often associated with the pathogenesis of Laron Syndrome, an autosomal recessive hereditary disorder characterized by severe growth retardation. Biochemically, patients present normal to high circulating GH levels, in presence of very low or undetectable IGF-I levels, which do not rise after rhGH treatment. Case presentation We describe the case of a 3.8 years old girl with symmetrical short stature (−3.76 SDS), low IGF-1 and IGFBP-3, in presence of normal GH levels. Parents were not relatives and there was no family history of short stature. During the second day of birth, she developed severe hypoglycaemia that required glucose infusion. She presented frontal bossing and depressed nasal bridge. IGF-1 generation test showed no response, suggesting a GH resistance evidence. In the hypothesis of Laron Syndrome, we decided to perform a molecular analysis of Growth Hormone Receptor (GHR) gene. This analysis demonstrated that the patient was compound heterozygote for two missense mutations. Conclusions GHR gene mutations are a well demonstrated cause of GH insensitivity. In heterozygous patients, probably the normal stature may be achieved by a compensatory mechanism of GH secretion or signalling. On the contrary, in homozygous or compound heterozygous patients these compensatory mechanisms are inadequate, and short stature may be the consequence.